1997
DOI: 10.1097/00005392-199703000-00117
|View full text |Cite
|
Sign up to set email alerts
|

p16 (CDKN2/MTS1) Gene Deletions are Rare in Prostatic Carcinomas in the United States and Japan

Abstract: Although slightly higher in Japan than in the United States, the frequency of p16 exon deletions in clinical prostatic carcinomas is very low, and probably is not important in the development of this neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…With regard to PCA, 60% deletions and 40–50% LOH have been described in cell lines [10, 13]; however, no deletions and a low frequency of mutations have been reported in primary PCA. A variety of studies using microdissected tissue specimens harbouring more than 80% tumor cells for PCR–SSCP detected mutations in only 2–5% of tumors investigated [14, 15, 16, 17, 18, 19, 20]. However, PCR–based approaches analyzing for homozygous deletions or LOH could be compromised by unavoidable contributions of normal cells, even in microdissected tissue specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to PCA, 60% deletions and 40–50% LOH have been described in cell lines [10, 13]; however, no deletions and a low frequency of mutations have been reported in primary PCA. A variety of studies using microdissected tissue specimens harbouring more than 80% tumor cells for PCR–SSCP detected mutations in only 2–5% of tumors investigated [14, 15, 16, 17, 18, 19, 20]. However, PCR–based approaches analyzing for homozygous deletions or LOH could be compromised by unavoidable contributions of normal cells, even in microdissected tissue specimens.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to 9p21, LOH has been described in 53% of prostate cancer specimens investigated [13]althogh genetic alterations have been shown to occur infrequently in primary PCA [14, 15, 16, 17, 18, 19, 20, 21]. However, the low frequency of genetic alterations in primary PCA might be explained by the PCR technique itself as PCR based approaches analyzing for deletions and mutations could be confounded by unavoidable contributions of normal cells even in microdissected tissue specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we have identified deletion regions on 9p, especially 9p21, which harbors p16 and other putative tumor-suppressor genes. Several investigators (Mangold et al, 1997;Gaddipati et al, 1997;Chen et al, 1996;Tamimi et al, 1996) have reported that p16 mutations are low or absent in prostate cancer. We did not analyze p16 mutations in this study since our aim was to identify the regions of deletion that may contain putative tumor-suppressor genes on chromosome 9p in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-cycle regulator Homozygous mutant mice develop hyperplasia and dysplasia of multiple tissues including prostate; loss of expression in human tumors correlates with tumor grade (Fero et al 1996;Kiyokawa et al 1996;Nakayama et al 1996;Guo et al 1997;Cordon-Cardo et al 1998;Cote et al 1998;De Marzo et al 1998a;Tsihlias et al 1998;Yang et al 1998) p16 Cell-cycle regulator Protein expression is up-regulated in carcinoma, but mutations are infrequent; limited information is currently available on the prostate phenotype of mutant mice or on the status of other INK family members (Chen et al 1996;Tamimi et al 1996;Chi et al 1997;Gaddipati et al 1997;Mangold et al 1997;Park et al 1997;Gu et al 1998) androgen-dependent cell that produces prostatic secretory proteins. At the molecular level, luminal cells are characterized by their expression of androgen receptor, as well as cytokeratins 8 and 18 and the cell surface marker CD57 (Brawer et al 1985;Nagle et al 1987;Verhagen et al 1988;Sherwood et al 1990;Liu et al 1997).…”
Section: Mxi1mentioning
confidence: 99%
“…However, with few exceptions (Chi et al 1997), most studies have reported that p16 is rarely mutated in primary prostate carcinomas, but is instead mutated in advanced metastatic disease (Chen et al 1996;Tamimi et al 1996;Gaddipati et al 1997;Mangold et al 1997;Park et al 1997;Gu et al 1998), although none of these studies examined the status of Rb in parallel. It has been suggested that in primary tumors, inactivation of p16 may occur by deletion of one allele, combined with promoter methylation of the remaining allele (Jarrard et al 1997).…”
Section: Altered Cell-cycle Regulatory Genesmentioning
confidence: 99%